Use of Magnetic Sensor for Groundwater Detection - Nurchim, Nurchim (LPPM of STIMIK ESQ, 2018)
This study aims for detect the existence of groundwater using magnetic sensor. I doing so, we calculated the value of the Earthâs magnetic field on the land area with large around 150 metres in Pandeyan sub district of Boyolali Regency. We used a linear magnetic hall sensor with SS49E type as our analytical proportion to the strength of the magnetic field. We made a magnetic measurement program who compiled in the microcontroller chip and the result will be show in the Liquid Crystal Display (LCD). When we took the data there, we found three spot with highest value, lowest value and fickle value of the magnetic field. After found these, we tried drill them to find the source of groundwater. The first spot as the highest with value of the strength of the magnetic field is 550 and we found the source of groundwater in a depth of 6 metres. The second spot as the lowest with value of the strength of the magnetic field is 549 and we found the source of groundwater in a depth more than 9 metres. The last spot is unique because the strength of the magnetic field always changing between the range 549 to 550 and we found the source of groundwater in a depth 7.5 metres. So that, it can be interpreted that the magnetic sensor can be used to find the source groundwater. The higher the value of the strength of the magnetic field then will be closer to groundwater.